2020
DOI: 10.3390/microorganisms8070977
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Inhibitor-Based Immunosuppression and COVID-19: Results from a Multidisciplinary Cohort of Patients in Northern Italy

Abstract: The role of immunosuppression in SARS-CoV-2-related disease (COVID-19) is a matter of debate. We here describe the course and the outcome of COVID-19 in a cohort of patients undergoing treatment with calcineurin inhibitors. In this monocentric cohort study, data were collected from the COVID-19 outbreak in Italy up to 28 April 2020. Patients were followed at our hospital for solid organ transplantation or systemic rheumatic disorders (RMDs) and were on calcineurin inhibitor (CNI)-based therapy. Selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 28 publications
2
42
0
3
Order By: Relevance
“…Experimental evidence suggested that CNIs, both cyclosporine and tacrolimus, inhibited viral replication of SARS-CoV through the inhibition of peptidyl-prolyl cis-trans isomerases [ 38 , 39 ]. A study of 14 patients with organ transplantation in Italy showed that clinical course of COVID-19 patients who received CNIs was generally mild and CNIs did not negatively affect the patients' outcome [ 40 ]. In our cohort, all patients received CNIs as maintenance immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence suggested that CNIs, both cyclosporine and tacrolimus, inhibited viral replication of SARS-CoV through the inhibition of peptidyl-prolyl cis-trans isomerases [ 38 , 39 ]. A study of 14 patients with organ transplantation in Italy showed that clinical course of COVID-19 patients who received CNIs was generally mild and CNIs did not negatively affect the patients' outcome [ 40 ]. In our cohort, all patients received CNIs as maintenance immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory drugs have been proposed as possible approaches and it has been suggested that immunosuppressive therapy may mitigate the manifestations of COVID-19. 5,6 Mesenchymal stem cells (MSCs) possess immunomodulatory properties as demonstrated by numerous in vitro and animal model studies. These effects are mediated by cytokines and soluble factors able to modulate the systemic but also the tissue inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…As there are no specific therapeutics for treating COVID‐19, in particular for the most severe cases complicated by ARDS or acute fulminant myocarditis, new innovative therapeutic approaches are urgently needed. Anti‐inflammatory drugs have been proposed as possible approaches and it has been suggested that immunosuppressive therapy may mitigate the manifestations of COVID‐19 5,6 . Mesenchymal stem cells (MSCs) possess immunomodulatory properties as demonstrated by numerous in vitro and animal model studies.…”
Section: Introductionmentioning
confidence: 99%
“…Since overactivated immune responses can be one of the causes of organ damage, the anti-inflammatory effects of immunosuppression can be protective, reducing the cytokine storm related to complications in COVID-19 [ 26 ]. In this context, it has been described that immunosuppressive therapy with calcineurin inhibitors in patients with solid organ transplantation or systemic rheumatic diseases promotes a clinical course in SARS-CoV-2 infection, which is generally mild, and with an apparently low risk of superinfection [ 27 ]. In addition, immunosuppression has not been evaluated as a risk factor for SARS or MERS [ 28 ].…”
Section: Discussionmentioning
confidence: 99%